Rivaroxaban for the treatment of venous thromboembolism in real life: A single-center prospective study. Issue 3 (January 2019) - Demelo-Rodríguez, Pablo; Galeano-Valle, Francisco; García-Fernández-Bravo, Irene; Piqueras-Ruiz, Sandra; Álvarez-Sala-Walther, Luis; del Toro-Cervera, Jorge
Abstract : Abstract: The clinical profile, evolution and complications of treatment with rivaroxaban in a cohort of patients presenting with venous thromboembolism (VTE) were analyzed in an observational, non-interventional and prospective study. A total of 111 patients were included in the study. Clinical data were collected from the medical history of the patients and recorded in a specific database. Mean age was 63.8 ± 17.4 years, 53.2% of patients were men, 55.9% had at least another concomitant condition, and 40.9% at least 1 VTE risk factor. 54.1% of patients presented with deep venous thrombosis, 32.4% with pulmonary embolism and 13.5% with both conditions simultaneously. The 61% of patients were admitted to hospital and mean hospital length-of-stay was 8.8 ± 9.9 days. After a mean follow-up 530 ± 464 days (median follow-up of 405 days), 3.9% of patients died and VTE recurrence occurred in 2.9% of patients. While receiving rivaroxaban, a first bleeding complication occurred in 8.1%; all events were minor bleeding. Our study supports the current literature data and confirms the similar results of real-life VTE patients with those enrolled in the rivaroxaban pivotal clinical trials. Rivaroxaban may facilitate outpatient treatment and might be considered as a first-line therapy for the management of VTE patients.